Serum and Urine Biomarkers Related to Kidney Fibrosis Predict Kidney Outcome in Czech Patients with IgA Nephropathy - Neprasova, Michaela; Maixnerova, Dita; Sparding, Nadja; Genovese, Federica; Karsdal, Morten Asser; Koprivova, Helena; Kollar, Marek; Suchanek, Miloslav; Hruskova, Zdenka; Tesar, Vladimir (International journal of molecular sciences, 2023)
We evaluated biomarkers related to kidney fibrosis for the outcome of patients with IgA nephropathy (IgAN). Clinical parameters (estimated glomerular filtration rate, hypertension, proteinuria) and histological findings were assessed in 134 patients with IgAN at the time of diagnosis and followed up prospectively (mean follow-up time, 56.5 months). We measured biomarkers of collagen and laminin turnover in serum and urine collected at the time of kidney biopsy using a novel enzyme-linked immunosorbent assay. Linear discriminant analysis and logistic regression models were used to predict the patient's kidney outcome. Five serum and urine biomarkers of laminin and collagen turnover (sLG1M, sPRO-C3, sPRO-C6, uPRO-C6/Cr, uC3M/Cr) could significantly differentiae IgAN patients with a worse prognosis. Clinical parameters (glomerular filtration rate (GFR), proteinuria) distinguished patients at risk of IgAN progression with a specificity of 87.3% and a sensitivity of 45.2% (area under the curve-AUC 0.751). The addition of the biomarkers significantly increased the prognostic ability with a specificity of 85.1% and a sensitivity of 73.3% (AUC 0.905). We have identified three serum (sLG1M, sPRO-C3, sPRO-C6) and two urinary markers (uPRO-C6/Cr, u-C3M /Cr) that significantly improve the prognostic ability of markers of kidney function to identify an IgAN patient's risk of progressing to ESKD.
Keywords: PRO-C3; proteinurie; Humans; Proteinuria; IgA nephropathy; biomarkers; ledviny; fibróza; Glomerular Filtration Rate; Fibrosis; Kidney; IgA nefropatie; fibrosis; lidé; Biomarkers; hodnoty glomerulární filtrace; Laminin; laminin; C3M; biologické markery; Czech Republic; extracellular matrix; PRO-C6; Glomerulonephritis, IGA; Česká republika; LG1M